Application of IoT and Machine Learning techniques for the assessment of thermal comfort perception. (August 2018) - Salamone, Francesco; Belussi, Lorenzo; Currò, Cristian; Danza, Ludovico; Ghellere, Matteo; Guazzi, Giulia; Lenzi, Bruno; Megale, Valentino; Meroni, Italo
Abstract: Thermal comfort is traditionally assessed by using the PMV index defined according to the EN ISO 7730:2005 where the user passively interacts with the surrounding environment considering a physic-based model built on a steady-state thermal energy balance equation. The thermal comfort satisfaction is a holistic concept comprising behavioral, physiological and psychological aspects. This article describes a workflow for the assessment of the thermal conditions of users through the analysis of their specific psychophysical conditions overcoming the limitation of the physic-based model in order to investigate and consider other possible relations between the subjective and objective variables.